Odpowiedzi

2010-02-19T16:23:17+01:00
F(x)=2x²+6x+4,5
g(x)=-x²+10x-25

rozwiąż nierówność f(-x)=4g(x)>0
f(-x)=2(-x)²+6(-x)+4,5=2x²-6x+4,5
4g(x)=4(-x²+10x-25)=-4x²+40x-100

f(-x)+4g(x).0
2x²-6x+4,5+(-4x²+10x-100)>0
2x²-6x+4,5-4x²+40x-100>0
-2x²+34x-95,5>0

a=-2, b=34, c=95,5
Δ=b²-4ac=(34)²-4*(-2)*95,5=1920
√Δ=√1920=√(64*30)=8√30

x₁=(-b+√Δ)/2a=(-34+8√30)/2*(-2)=(-34+8√30)/-4=2(-17+4√30)/-4=
=(17-4√30)/2

x₂=(-b-√Δ)/2a=(-34-8√30)/2*(-2)=(-34-8√30)/-4=2(-17-4√30)/-4=
=(17+4√30)/2

wykresem jest parabola, która ma ramiona skierowane w dół (a=-2), a
x₁=(17-4√30)/2
i
x₂=(17+4√30)/2
są miejscami zerowymi

czyli
f(-x)+4g(x)>0, gdy:
x∈( (17-4√30)/2 ;(17+4√30)/2 )